Mapping China's time-varying house price landscape - Michael Funke; Danilo Leiva-Leon; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
The recent increase in China's house prices at the national level masks tremendous variation at the city level – a feature largely overlooked in the macroprudential literature. This paper considers the evolving heterogeneity in China's house price dynamics across 70 cities and assess the main deter-minants. We gauge the heterogeneity of house price dynamics using a novel regime-switching modelling approach to estimate the time-varying patterns of China's city-level housing price synchronization. After sorting city-level housing prices into four clusters sharing similar cyclical features, we see that each group shows increasing synchronization in the years leading up to 2015, and a decoupling pattern thereafter. We document high synchronization within each of the clusters of cities, but low synchronization among them. The empirical evidence suggests that differentials in the growth of households, income, investment and even differences in air quality explain housing price synchronization among cities.
URN:NBN:fi:bof-201712111682
Keywords: E31; E32; C32; 330